Modeling of a Photovoltaic-Fuel Cell Battery for Hybrid Electric Vehicle - Dr.K.S.Yamuna, Dr.G.Suresh, A.Kausalya (International Journal of Advanced Science and Technology, 2020)
The development towards electric vehicle is growing enormously due to global warming phenomenon. So in order to reduce the global warming, electric vehicle is moving towards Renewable Energy Sources (RES) such as Solar and fuel cell, Hence this work modeled and analysed the achievability of hybrid PV-FC source for EV. This system comprises PV system, FC and a Boost converter unit and is modeled using MATLAB Simulink environment. From the results, it is concluded that this system can effectively work in different situations and exhibits better fuel economy.